KSA DEVELOPMENT IN THE AB ENGLISH LANGUAGE PRACTICUM - Meneses, Ma. Celina Eladia G. (PEOPLE: International Journal of Social Sciences, 2016)
In response to the prevailing mismatch between education and industry needs, the AB English program of Bicol University was revised to include a student internship program, the Language Practicum, which attempts to augment classroom learning with actual knowledge, skills, and attitudes (KSAs) necessary in the workplace. This study assessed the level of attainment of these learning domains for the holistic development of the students, as reported by the trainees themselves and by their sponsoring agencies, towards determining the success of the entire program. A focus-group discussion provided a validation of results of both assessments. Applying the evaluation theory by Stufflebeam and Shinkfield, and using the descriptive-evaluative method involving a total enumeration of the trainees and their supervisors, the study revealed an outstanding assessment of KSA development, both in the point of view of the trainees who came up with a mean rating of 4.58, and that of the supervisors who arrived at a mean rating of 4.56. Slight inadequacy was registered by the trainees in terms of skills, which they rated as 4.50 or superior, but was refuted by their supervisors who rated them an average of 4.53 or outstanding. Findings point to the conclusions that the Language Practicum was highly successful, and that industry partnership is important in the maximum development of students’ knowledge, skills, and attitudes. The program is recommended for continuance.